“No es solo una crisis sanitaria”. Los periodistas brasileños enfrentan importantes riesgos profesionales y personales mientras denuncian la pandemia - Melani Rocha, Paula; Kondlatsch, Rafael; Castillo, Antonio (Estudios sobre el Mensaje Periodístico, 2023)
This paper examines the preliminary results and findings of Brazil’s journalism and the COVID 19 pandemic, conducted under The Global Risk Journalism Hub (GRJH) international collaboration project. The reflection is framed around the mission statement of the GRJH – to find out about the challenges journalists worldwide experience when covering globalized “risks,” such as health pandemics, environmental crises, and humanitarian conflicts. In the context of a globalized digital data ecosystem, the fundamental aim of this paper is to examine current journalistic practice to lay the grounds for the development of new models of international global crisis reporting. This paper is based on a survey and qualitative interviews applied to a selected group of 20 Brazilian journalists. These data are examined through the research methodology and theoretical framework designed by The Global Risk Journalism Hub international research collaboration